Selective reprogramming of regulatory T cells in solid tumors can strongly enhance or inhibit tumor growth - Alfar, Rami; Napoleon, John V.; Shahriar, Imrul; Finnell, Richard; Walchle, Cole; Johnson, Austin; Low, Philip S. (Frontiers in Immunology, 2023)
Folate receptor delta (FRδ) has been used as a biomarker for regulatory T cells (Tregs), because its expression is limited to Tregs and ovum. Although FRδ is unable to bind folate, we have used molecular docking software to identify a folate congener that binds FRδ with high affinity and have exploited this FRδ-specific ligand to target attached drugs (imaging agents, immune activators, and immune suppressors) specifically to Tregs in murine tumor xenografts. Analysis of treated tumors demonstrates that targeting of a Toll-like receptor 7 agonist inhibits Treg expression of FOXP3, PD-1, CTLA4, and HELIOS, resulting in 40-80% reduction in tumor growth and repolarization of other tumor-infiltrating immune cells to more inflammatory phenotypes. Targeting of the immunosuppressive drug dexamethasone, in contrast, promotes enhanced tumor growth and shifts the tumor-infiltrating immune cells to more antiinflammatory phenotypes. Since Tregs comprise <1% of cells in the tumor masses examined, and since the targeted drugs are not internalized by cancer cells, these data demonstrate that Tregs exert a disproportionately large effect on tumor growth. Because the targeted drug did not bind to Tregs or other immune cells in healthy tissues, the data demonstrate that the immunosuppressive properties of Tregs in tumors can be manipulated without causing systemic toxicities associated with global reprogramming of the immune system.